Language, Identity, and Power: A Sociolinguistic Inquiry into Code-Switching Practices in South Asian Multilingual Communities - Raja Muhammad Shoaib Khan; Malik Umer Ajmal; Talha Idrees (English Lecturers and Teachers Association (ELTA), 2026)
This paper examines the relationship between language, identity, and power through the lens of code-switching in South Asian multilingual contexts. Adopting a theoretical and interpretive sociolinguistic approach, the study does not rely on empirical or corpus-based data but instead draws on hypothetical and illustrative cases grounded in established sociolinguistic theory. Integrating perspectives from variationist, interactional, and critical sociolinguistics, the paper analyzes how code-switching functions as a communicative resource through which speakers negotiate identity, manage interactional meanings, and engage with symbolic power. The analysis suggests that code-switching in South Asian postcolonial societies cannot be adequately understood through deficit models of bilingualism; rather, it operates as a socially meaningful practice shaped by historical, educational, and ideological hierarchies. By conceptualizing code-switching as a dynamic and situated practice, the study highlights its implications for language policy, pedagogy, and debates on identity and power in multilingual societies. Keywords: Code-switching, Multilingualism, Sociolinguistics, Identity construction, Symbolic power,